2020
DOI: 10.3346/jkms.2020.35.e116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bone Mineral Density on the Incidence of Age-Related Vertebral Fragility Fracture

Abstract: Background: Vertebral fragility fracture (VFF) is a common fracture related to osteoporosis. However, VFF might be asymptomatic and often occurs in patients without osteoporosis. Therefore, we investigated the characteristics of age-related VFF and their correlation with bone mineral density (BMD). Furthermore, we analyzed other factors affecting VFF Methods: Medical records from a single center were retrospectively reviewed for 2,216 patients over 50 years old with vertebral fractures conservatively treated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…A recent study reported that BMD was a risk factor for VCFs, but the association of BMD and VCFs was not high, and age could be associated with VCFs even in patients with normal BMD. [ 43 ] Another study regarding osteoporotic VCFs stated that the progression of canal encroachment on magnetic resonance imaging was correlated with age but not with BMD, and the quality of the bone declines with aging even if BMD remains high. [ 6 ] Traumatic VCFs were unrelated to osteoporosis and the decrease in vertebral heights would have progressed without the influence of BMD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that BMD was a risk factor for VCFs, but the association of BMD and VCFs was not high, and age could be associated with VCFs even in patients with normal BMD. [ 43 ] Another study regarding osteoporotic VCFs stated that the progression of canal encroachment on magnetic resonance imaging was correlated with age but not with BMD, and the quality of the bone declines with aging even if BMD remains high. [ 6 ] Traumatic VCFs were unrelated to osteoporosis and the decrease in vertebral heights would have progressed without the influence of BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were associated with a traffic accident, high-energy trauma, back pain treated with medication in the last 3 months, and other comorbidities affecting back pain were excluded ( Figure 1 ). Demographic data including age, body mass index (BMI), and bone mineral density (BMD) were investigated [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“… 2 3 Thus, these agents significantly reduce bone turnover markers (BTMs), increase BMD, and reduce risk for fracture. 2 3 4 5 6 Despite similar effects on bone resorption, the agents have distinct mechanisms of action. 7 …”
Section: Introductionmentioning
confidence: 99%